Isolation, Identification and Characterization of Escherichia Coli O157:H7 from Poultry Meat - A Worldwide Public Health Threat! - Tanveer, Adeela; Muneer, Bushra; Mehboob, Khawar; Rafique, Rehan; Sharif, Fozia (Infectious Diseases Journal of Pakistan, 2023)
Background: Food borne and meat borne diseases are considered as a major and most important challenge to the public health. Each year millions of human deaths in the world can be attributed to the Escherichia coli contaminated foods. Poultry meat is one of the major sources of food borne illness caused by E. coli. Hence this study was conducted to isolate, identify and characterize Escherichia Coli O157:H7 from Poultry Meat because of its public health significance, moreover to aware people from the spread of meat borne infections. Methods: Poultry meat samples (chest piece, leg piece, frozen meat, minced chicken meat) were collected from different retail outlets located at Lahore city and processed for isolation of Escherichia Coli on different culture media. The positive isolates for E. coli were microbiologically identified on the basis of morphology, and confirmed by different biochemical reactions. Furthermore, all the confirmed isolates through biochemical tests were subjected to polymerase Chain reaction (PCR) analysis for presence of E. coli O157:H7. Results: Results showed that overall by traditional culture methods 29 chicken samples on nutrient agar, 21 on MacConkey agar, 15 on SMAC and 15 on BGA were found positive showing 36.25%, 26.25%, 26.25%, 18.75% percentage positivity. A total of 11 samples by biochemical tests and 6 samples through PCR were found positive indicating the 13.75 % and 7.5 % percentage positivity in chicken meat samples respectively. Thus these results indicated that E coli O157:H7 is prevalent in Lahore, Pakistan with highest percentage of E. coli O157:H7 in minced chicken meat. Conclusion: E. coli O157:H7 is prevalent in poultry meat in our country as a great hazard to public health. Polymerase chain reaction is sensitive, specific and efficient way for confirmation of E. coli. Hygienic measures are recommended as of core importance to avoid food borne illnesses. Key words: Poultry Meat, Polymerase chain reaction (PCR), E. coli O157:H7, Food safety, Public health